Axial-Symmetry Numerical Approaches for Noise Predicting and Attenuating of Rifle Shooting with Suppressors - Shi-Wei Lo; Chang-Hsien Tai; Jyh-Tong Teng (Journal of Applied Mathematics)
The moving bullet out of a rifle barrel is propelled by a fired explosive charge. Subsequently, a disturbed muzzle blast wave is initiated which lasts several milliseconds. In this study, axially symmetric, unsteady, Large Eddy Simulation (LES), and Ffowcs Williams and Hawkins (FWH) equations were solved by the implicit-time formulation. For the spatial discretization, second order upwind scheme was employed. In addition, dynamic mesh model was used to where the ballistic domain changed with time due to the motion of bullet. Results obtained for muzzle flow field and for noise recorded were compared with those obtained from experimental data; these two batches of results were in agreement. Five cases of gunshot including one model of an unsuppressed rifle and four models of suppressors were simulated. Besides, serial images of species distributions and velocity vectors-pressure contours in suppressors and near muzzle field were displayed. The sound pressure levels (dB) in far field that were post-processed by the fast Fourier transform (FFT) were compared. The proposed physical model and the numerical simulations used in the present work are expected to be extended to solve other shooting weapon problems with three-dimensional and complex geometries.